Peran Fear of Missing Out Terhadap Phubbing pada Siswa SMA Kristen di Kota Surakarta - Ardha Strinaricwari; Sujoko Sujoko; Yustinus Joko Dwi Nugroho (INSIGHT: JURNAL PEMIKIRAN DAN PENELITIAN PSIKOLOGI, 2023)
Technological developments make it easy for Generation Z, namely high school students, to fulfill their social needs, to actualize themselves, and to connect with many individuals both around them and far away. This then becomes a need that continues to be sought and must be met which triggers the indication of Fear of Missing Out. The fulfillment of these social needs is then found through social media on their gadgets. From here, Phubbing's behavior arises because they are busy looking for information and want to connect with their friends in cyberspace.This study aims to determine the relationship between Fear of Missing Out on Phubbing in Christian high school students in the city of Surakarta. The hypothesis proposed in this study is "There is a role of Fear of Missing Out on Phubbing in Christian high school students in the city of Surakarta." The research was carried out using a quantitative method and using a clustered random sampling technique. The sample used was 234 Christian high school students in Surakarta who were in grades 1, 2 and 3. The measuring instrument of this study used the Fear of Missing Out scale and the Phubbing scale. The data analysis method used is the non-parametric correlation of Kendall Tau with the help of SPSS 21.0 for windows release. The results of data analysis showed the correlation coefficient value of 0.317 with p = 0.000 (p 0.05). This proves that there is a positive relationship between Fear of Missing Out and Phubbing, the higher the Fear of Missing Out, the higher the Phubbing behavior that appears. So in this case the proposed hypothesis is accepted.